Growth and Properties of Defect‐Chalcopyrite CdGa2Se4 Crystals. Issue 16 (24th April 2018) - Wang, Zhenyou; Wu, Haixin; Ni, Youbao B.; Huang, Changbao; Mao, Mingsheng; Chen, Shijing; Ma, Jiaren
Abstract: CdGa2 Se4 crystal, with the structure of defect‐chalcopyrite, is a promising optical and photoelectric material. Single crystal with size of Φ11×60 mm 3 was grown successfully by vertical Bridgman method. The as‐grown crystal was characterized with X‐ray diffraction (XRD), energy dispersive X‐ray Spectroscopy (EDS), and transmission spectra etc. The results show that the crystalline quality of the crystal is very good, and the atomic ratio is Cd:Ga:Se=1:2.12:4.05, which is close to the ideal stoichiometry. The crystalline quality and the chemical composition of the cracked section near the end of the crystal were also measured and the cracking reason was analyzed. The transparency range of the crystal was revealed for the first time. The transmittance of a 3.6 mm sample is above 65% in the range of 5 to 12 μm, which demonstrate the high optical quality of the crystal. Based on the transmission spectra, the refractive index and the energy bandgap were calculated to be 2.5 and 1.97 eV respectively. Abstract : Pure CdGa2 Se4 polycrystalline were synthesized and single crystals with size of Φ11×60 mm 3 were grown by vertical Bridgman method. The crystalline quality, the chemical composition and the optical properties were investigated. To our knowledge, the transparency range of the crystal was revealed for the first time, which is 0.61‐20.9 μm. The refractive index and the energy bandgap were calculated to be 2.5 and 1.97 eV, respectively.